Effects of Exosomes on Neurological Function Recovery for Ischemic Stroke in Pre-clinical Studies: A Meta-analysis - Huang, Mudan; Hong, Zhongqiu; Xiao, Chongjun; Li, Lili; Chen, Lilin; Cheng, Shimei; Lei, Tingting; Zheng, Haiqing (Frontiers in Cellular Neuroscience, 2020)
Background: Exosomes, especially stem cell-derived exosomes, have been widely studied in preclinical research of ischemic stroke. However, their pooled effects remain inconclusive. Methods: Relevant literature concerning the effects of exosomes on neurological performance in a rodent model of ischemic stroke were identified via searching electronic databases including PubMed, Embase and Web of Science. The primary outcomes included neurological function scores (NFS) and infarct volume (IV), and the secondary outcomes were several pro-inflammatory factors as well as TUNEL-positive cells. Subgroup analyses regarding several factors potentially influencing the effects of exosomes on NFS and IV were also conducted. Results: We identified 21 experiments from 18 studies in the meta-analysis. Pooled analyses showed the positive and significant effects of exosomes on NFS (SMD -2.79; 95% CI -3.81 to -1.76) and IV (SMD -3.16; 95% CI -4.18 to -2.15). Our data revealed the effects of exosomes on neurological outcomes in rodent stroke model might be related to routes of administration and exosomes sources. In addition, there were significant attenuation in pro-inflammatory factors, including IL-6, TNF-α and IL-1β, and TUNEL-positive cells when undergoing exosomes treatment. Conclusion: Cell-derived exosomes treatment demonstrated statistically significant improvements on structural and neurological function recovery in animal models of ischemic stroke. Our results also provide relatively robust evidence supporting cell-derived exosomes as a promising therapy to promote neurological recovery in stroke individuals.